2023
DOI: 10.3390/microorganisms11051232
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics, Prebiotics, and Synbiotics Utilization in Crayfish Aquaculture and Factors Affecting Gut Microbiota

Abstract: Aquaculture is affected by numerous factors that may cause various health threats that have to be controlled by the most environmentally friendly approaches. In this context, prebiotics, probiotics, and synbiotics are frequently incorporated into organisms’ feeding rations to ameliorate the health status of the host’s intestine, enhancing its functionality and physiological performance, and to confront increasing antimicrobial resistance. The first step in this direction is the understanding of the complex mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 137 publications
0
2
0
Order By: Relevance
“…The advancements in targeted delivery systems have facilitated the precise localization of probiotics to their intended destinations, enabling them to exert favorable effects [12]. Multiple studies have been carried out on cultured animals, substantiating the influence of diverse probiotics on the abundance of beneficial bacteria and the reduction in pathogenic burden [13,14]. Employing probiotics has been demonstrated to be an effective approach in enhancing shellfish health and productivity [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advancements in targeted delivery systems have facilitated the precise localization of probiotics to their intended destinations, enabling them to exert favorable effects [12]. Multiple studies have been carried out on cultured animals, substantiating the influence of diverse probiotics on the abundance of beneficial bacteria and the reduction in pathogenic burden [13,14]. Employing probiotics has been demonstrated to be an effective approach in enhancing shellfish health and productivity [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Employing probiotics has been demonstrated to be an effective approach in enhancing shellfish health and productivity [15,16]. Various genera of bacteria are used as probiotics in aquaculture, including Aeromonas, Alteromonas, Arthrobacter, Bifidobacterium, Bacillus, Clostridium, Enterococcus, Lactobacillus, Paenibacillus, Phaeobacter, Pseudoalteromonas, Pseudomonas, Rhodosporidium, Roseobacter, Streptomyces, and Vibrio [14]. Lactic acid bacteria (LAB) have become increasingly used as probiotics in aquaculture over the past decade [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, dietary fortification of piglet diets with selenium and probiotics is very beneficial, making it a feasible nutritional supplement under conditions of heat stress during the summer season [ 63 ]. In aquatic invertebrates, it has been proven that probiotics’ addition triggers a thermal and metabolic stress response, substantially improving the welfare of the reared organism [ 64 ]. Studies conducted on the feeding of terrestrial productive animals—which were subjected to heat stress conditions—with an enriched diet with selenium and probiotics, demonstrated that the HSP expression was affected in both chicken [ 65 ] and piglets [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The seaweed and soybean dietary components contain bioactive compounds such as isoflavones, saponins, and oligosaccharides in soybean [ 98 100 ], and polysaccharides, polyphenols, phycobiliproteins, and phlorotannins in seaweed [ 101 103 ]. These compounds can exert prebiotic effects, influencing the composition of the gut microbiota [ 104 ]. Prebiotics are essentially non-digestible substances that, when consumed, foster beneficial changes in the gut microbiome, promoting the development of a more favorable microbial community [ 105 ].…”
Section: Discussionmentioning
confidence: 99%